2019
DOI: 10.1017/jog.2019.22
|View full text |Cite
|
Sign up to set email alerts
|

GlacierMIP – A model intercomparison of global-scale glacier mass-balance models and projections

Abstract: Global-scale 21st-century glacier mass change projections from six published global glacier models are systematically compared as part of the Glacier Model Intercomparison Project. In total 214 projections of annual glacier mass and area forced by 25 General Circulation Models (GCMs) and four Representative Concentration Pathways (RCP) emission scenarios and aggregated into 19 glacier regions are considered. Global mass loss of all glaciers (outside the Antarctic and Greenland ice sheets) by 2100 relative to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
212
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 222 publications
(226 citation statements)
references
References 58 publications
10
212
1
3
Order By: Relevance
“…The contribution to GMSL from glaciers and ice caps melting generally corroborate the findings by Hock et al (2019), who found that by the end of the 21 st century mountain glaciers and ice caps lose between 11-25 % (RCP2.6) and 25-47 % (RCP8.5) of their volume. For scenario MMCP8.5, our results are below the average estimates at the end of the 21 st century because of 325 the rather low climate sensitivity in LOVECLIM.…”
Section: Discussionsupporting
confidence: 87%
“…The contribution to GMSL from glaciers and ice caps melting generally corroborate the findings by Hock et al (2019), who found that by the end of the 21 st century mountain glaciers and ice caps lose between 11-25 % (RCP2.6) and 25-47 % (RCP8.5) of their volume. For scenario MMCP8.5, our results are below the average estimates at the end of the 21 st century because of 325 the rather low climate sensitivity in LOVECLIM.…”
Section: Discussionsupporting
confidence: 87%
“…To assess glacier evolution under future climate scenarios, geodetic glacier mass balance observations can be used to calibrate and validate glacier evolution model projections. These models estimate ∼36-87% mass loss for HMA glaciers by 2100, depending on the glacier evolution model, climate forcing, and representative concentration pathway (RCP) scenario (Kraaijenbrink et al, 2017;Hock et al, 2019). This loss will lead to a significant decrease in seasonal glacier meltwater runoff, with important implications for downstream stakeholders (Huss and Hock, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Glaciers are arguably one of the most important icons of climate change, being climate proxies which can clearly depict the evolution of climate for the global audience (IPCC, 2018). For the coming decades, mountain glaciers will be some of the most important contributors to sea level rise and will most likely drive important changes in the hydrological regime of glaciarized catchments (Beniston et al, 2018;Vuille et al, 2018;Hock et al, 2019). The reduction in ice volume may produce an array of consequences which requires to be properly predicted.…”
Section: Introductionmentioning
confidence: 99%